IMPLEMENTASI ETIKA BISNIS ISLAM PADA UMKM BURUNG PUYUH PETELUR DI DESA TRIBUNGAN KECAMATAN MANGARAN KABUPATEN SITUBONDO - Romzatul Widad (IZZI: Jurnal Ekonomi Islam, 2023)
The purpose of this study was to determine the application of business ethics in quail UMKM. The method used is a qualitative method with field studies. The results of the study show that the application seen from the principle of justice does not differentiate between other suppliers, the principle of honesty of quail egg scales according to weight and not reduced and added. The principle of freedom gives freedom to buy quail eggs. The principle of responsibility serves wholeheartedly and the principle of communication undergoes good and honest communication